Analytical and functional approaches to assess the immunogenicity of gluten proteins - Mamone, Gianfranco; Di Stasio, Luigia; Vitale, Serena; Picascia, Stefania; Gianfrani, Carmen (Frontiers in Nutrition, 2023)
Gluten proteins are the causative agent of Celiac Disease (CD), a life-long and worldwide spread food intolerance characterized by an autoimmune enteropathy. Although nutritionally poor for humans, gluten proteins are a real treasure for food industry, as they confer a unique visco-elasticity properties to dough and to gluten-based food products. Gluten is a complex mixture of high homologous water-insoluble proteins characterized by high content of glutamine and proline aminoacids. This peculiar chemical property confers to gluten proteins a marked resistance to degradation by gastrointestinal proteases. As consequence of that, large gluten fragments are released in gut lumen with potential to activate inflammatory T cells in CD-predisposed individuals. So far, a large number of peptides eliciting inflammatory responses in celiacs has been identified in all gluten protein families. The complete delucidation of gluten immunogenic peptides have a great relevance for the development of pharmacological therapies alternative to the gluten exclusion diet, the only efficacious treatment for CD, or for searching of cereal species with reduced or null toxicity for celiacs. This review will comprehensively overview the analytical and functional methods to assess the immunogenic peptides in gluten proteins from different sources, including cereal wheats and complex food matrices. The analytical workflow to dissect the profile of peptides includes the validated in vitro physiologic oral-gastro-intestinal digestive model and characterization by proteomic and immunochemical analysis, such as liquid chromatography high resolution mass spectrometry (LC-M/MS) and R5/G12 competitive ELISA. The capability of digested gluten peptides to stimulate an inflammatory reaction includes assays both in vitro on intestinal human T cells, and ex vivo on peripheral blood of CD volunteers after a brief gluten oral challenge.